Sintering behaviour of forsterite-doped hydroxyapatite ceramics - Ramesh S.; Virik N.S.; Bang L.T.; Niakan A.; Tan C.Y.; Purbolaksono J.; Yap B.K.; Ramesh S.; Teng W.D. (Institute of Chemical Technology, 2023)
Ball milling; Ceramic materials; Density (specific gravity); Elastic moduli; Fracture; Grain growth; Grain size and shape; Hydroxyapatite; Mechanical properties; Microstructure; Olivine; Phase stability; Sintering; Vickers hardness; Bulk density; Doped hydroxyapatites; Forsterites; Grain size; Microstructure and mechanical properties; Powder mixing; Relative density; Sintered body; Fracture toughness